Israel's rapid rollout of vaccinations for COVID-19 - Bruce Rosen; Ruth Waitzberg; Avi Israeli (BMC, 2021)
Abstract As of the end of 2020, the State of Israel, with a population of 9.3 million, had administered more COVID-19 vaccine doses than all countries aside from China, the US, and the UK. Moreover, Israel had administered almost 11.0 doses per 100 population, while the next highest rates were 3.5 (in Bahrain) and 1.4 (in the United Kingdom). All other countries had administered less than 1 dose per 100 population. While Israel's rollout of COVID-19 vaccinations was not problem-free, its initial phase had clearly been rapid and effective. A large number of factors contributed to this early success, and they can be divided into three major groups. The first group of factors consists of long-standing characteristics of Israel which are extrinsic to health care. They include: Israel's small size (in terms of both area and population), a relatively young population, relatively warm weather in December 2020, a centralized national system of government, and well-developed infrastructure for implementing prompt responses to large-scale national emergencies. The second group of factors are also long-standing, but they are health-system specific. They include: the organizational, IT and logistical capacities of Israel's community-based health care providers, the availability of a cadre of well-trained, salaried, community-based nurses who are directly employed by those providers, a tradition of effective cooperation between government, health plans, hospitals, and emergency care providers - particularly during national emergencies; and support tools and decisionmaking frameworks to support vaccination campaigns. The third group consists of factors that are more recent and are specific to the COVID-19 vaccination effort. They include: the mobilization of special government funding for vaccine purchase and distribution, timely contracting for a large amount of vaccines relative to Israel's population, the use of simple, clear and easily implementable criteria for determining who had priority for receiving vaccines in the early phases of the distribution process, a creative technical response that addressed the demanding cold storage requirements of the Pfizer-BioNTech COVID-19 vaccine, and well-tailored outreach efforts to encourage Israelis to sign up for vaccinations and then show up to get vaccinated. While many of these facilitating factors are not unique to Israel, part of what made the Israeli rollout successful was its combination of facilitating factors (as opposed to each factor being unique separately) and the synergies it created among them. Moreover, some high-income countries (including the US, the UK, and Canada) are lacking several of these facilitating factors, apparently contributing to the slower pace of the rollout in those countries.